UMKM GO DIGITAL AS AN ANDROID MARKETING STRATEGY FOR LOCAL MICRO ENTERPRISES - Marliasari, Marliasari; Rahayu, Lusia Septia Eka Esti; Rasid, Muhammad; Junaidi, Muhammad (Journal of Software Engineering and Technology., 2025)
The development of information technology is in line with the continuous progress of the times, creating innovation in every generation. One of the most rapidly developing aspects is the world of telecommunications, with mobile phones or Android smartphones as one example. Smartphones that use Android-based operating systems function like computers with Windows operating systems, but offer higher mobility and accessibility. To maximize the potential of smartphones, applications are needed that support their functionality. This study aims to implement an application system specifically designed to help local micro-businesses market their products more efficiently. Through this application, buying and selling transactions become flexible and effective, allowing sellers to manage and increase their sales better. The development method used in this study is the waterfall model, which is systematic and structured. In designing applications for local micro-businesses, there are various menus designed to improve the user experience, including the login menu, homepage, order input, payment, and user profile. With this approach, it is hoped that the application can provide real solutions for micro-business actors in facing marketing challenges in the digital era.